2017
DOI: 10.1080/02656736.2017.1394502
|View full text |Cite
|
Sign up to set email alerts
|

Head-out immersion in hot water increases serum BDNF in healthy males

Abstract: The present findings suggested that the increase in BDNF during 20-min hot-HOI was induced by hyperthermia through enhanced production, rather than by changes in permeability of the blood-brain barrier (BBB), platelet clotting mechanisms or secretion from monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
4
30
3
Order By: Relevance
“…A recent study provides exciting evidence for the possible contribution of the brain and/or vascular endothelial cells to circulating BDNF independent of exercise. Kojima et al (2017) found that 20 minutes of head-out immersion in hot water significantly increases serum BDNF, which supports previous findings that exercise performed in the heat results in significantly greater increases in serum BDNF compared to a normothermic environment (Goekint et al 2011, Lee et al 2014. These findings are especially compelling because serum BDNF increased without an accompanying increase in platelets, suggesting exclusive contribution from cellular sources (Watson 2005).…”
Section: R a F T Shear Stress Elevation For Endothelial Release Of supporting
confidence: 82%
“…A recent study provides exciting evidence for the possible contribution of the brain and/or vascular endothelial cells to circulating BDNF independent of exercise. Kojima et al (2017) found that 20 minutes of head-out immersion in hot water significantly increases serum BDNF, which supports previous findings that exercise performed in the heat results in significantly greater increases in serum BDNF compared to a normothermic environment (Goekint et al 2011, Lee et al 2014. These findings are especially compelling because serum BDNF increased without an accompanying increase in platelets, suggesting exclusive contribution from cellular sources (Watson 2005).…”
Section: R a F T Shear Stress Elevation For Endothelial Release Of supporting
confidence: 82%
“…The number of measurements used to test the effects of dependent variables ranged from two to six. The study by Brunt et al [25] had the highest number of measurements (six), including one pre-test and five post-test measurements. Even in cases with a single experimental treatment, repeated (two or four) measurements were performed to investigate the short- and long-term effects of water immersion.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies by Shimodozono et al [19], Bailey et al [20], and Hu et al [23], female subjects were allowed to participate in the experiment during the follicular phase of their menstrual cycle in order to control for the temperature changes due to the menstrual cycle, while middle-aged women were only enrolled if they were in the menopausal stage. In a study by Brunt et al [25], urinalysis was performed on female subjects during all experimental procedures to accurately identify their pregnancy status by assessing the level of human chorionic gonadotropin, a pregnancy hormone. In addition, other lifestyle factors, such as medication use, drinking status, smoking status, exercise status, caffeinated beverage intake, estrogen hormone therapy, and regular thermal therapy, were assessed in order to select a homogenous study population and control for the confounding effects on the treatment effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations